New species of Hermanella complex (Ephemeroptera: Leptophlebiidae) from Brazilian Atlantic Forest - Nascimento, Jeane M. C. Do; Salles, Frederico F. (Zootaxa, 2013)
In the present work, based on material from Brazilian Atlantic Forest, four new species of the Hermanella complex are described. The main characteristics that distinguish the new species from its congeners are, in Hermanella amere sp. nov.: (1) subgenital plate yellow, with wide projection near base of forceps; (2) penis lobe with ventral, robust, posterioly directed spine; in Hermanella nigra sp. nov.: (1 ) subgenital plate brown washed with gray, with wide projection near inner base of forceps; (2) penis lobe with a distomedial membranous projection and ventral, robust, posteriorly directed spine; in Hylister obliquus sp. nov.: (1) subgenital plate yellowish brown, with pointed projection near inner base of forceps; (2) penis lobe with ventral, short, narrow, posteromedially directed spine; in Traverella insolita sp. nov.: (1) subgenital plate strongly projected posteriorly, forming three broad and short projections; (2) penis lobe laterally sinuous and apically rounded, with a ventral, long, narrow spine curved toward the midline of the body. Modified keys of male imagos are provided for the three genera, whereas comments regarding their taxonomy are presented. Additionally, Hermanella mazama (Nascimento, Mariano & Salles 2012 in Lima et al. 2012), comb. nov., is proposed.